2018
DOI: 10.1016/j.psychres.2018.08.106
|View full text |Cite
|
Sign up to set email alerts
|

History of childhood emotional abuse predicts lower resting-state high-frequency heart rate variability in depressed women

Abstract: Childhood emotional abuse impairs emotion regulation and increases risk for major depressive disorder in adulthood. Mounting evidence suggests that decreased resting-state high-frequency heart rate variability, an index of parasympathetic function, represents a transdiagnostic biomarker of emotion dysregulation. We propose that adults with histories of major depressive disorder and childhood emotional abuse represent a subpopulation at particularly high risk to exhibit deficits in parasympathetic control. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…Given there are sex differences in ANS functioning (see Beauchaine, 2001), the ANS alterations currently linked to depressive and anxiety symptoms may not generalize to men. There is also evidence ANS alterations associated with concurrent psychopathology may be accounted for by early life experiences (childhood abuse) (Stone, Amole, Cyranowski, & Swartz, 2018). Future research is needed to disentangle ANS alterations that predict risk for psychopathology versus reflect correlates of concurrent distress.…”
Section: T a B L E 3 Associations Between Autonomic Indices And Intermentioning
confidence: 99%
“…Given there are sex differences in ANS functioning (see Beauchaine, 2001), the ANS alterations currently linked to depressive and anxiety symptoms may not generalize to men. There is also evidence ANS alterations associated with concurrent psychopathology may be accounted for by early life experiences (childhood abuse) (Stone, Amole, Cyranowski, & Swartz, 2018). Future research is needed to disentangle ANS alterations that predict risk for psychopathology versus reflect correlates of concurrent distress.…”
Section: T a B L E 3 Associations Between Autonomic Indices And Intermentioning
confidence: 99%
“…For example, it is well known that stress is a robust predictor for MDD, and interpersonal stressors can play a central role in the onset of a major depressive episode (Auerbach et al, 2014;Tottenham & Galvan, 2016). Early life stress is also associated with alterations in autonomic stress regulation, including reduced RSA (e.g., Cyranowski et al, 2011;Miskovic et al, 2009;Stone et al, 2018) and less flexible patterns of parasympathetic activity, as indexed by less vagal withdrawal to a sad film and impaired physiological recovery during mood repair among adolescents with depression histories (Daches et al, 2017). It is also well-established that early life adversity, such as child maltreatment, can disrupt neural processing of reward (e.g., Auerbach et al, 2014;Novick et al, 2018).…”
Section: Interactions Across Functional Domains: Reward and Stressmentioning
confidence: 99%
“…Current models assume that ACEs increase CVD risk by altering long-term patterns of autonomic regulation by disturbing the sympathetic and parasympathetic balance (7,23), characterized by enduring higher sympathetic activity and lowered parasympathetic activity. Multiple studies have shown associations between ACEs and HRV, generally finding lower HRV to be associated with ACEs, but not all findings in nonclinical, depressed and adolescent samples have been consistent (24)(25)(26)(27)(28). The association between ACEs and BRS has not been examined before.…”
Section: Introductionmentioning
confidence: 99%